The Spot 42 RNA: A regulatory small RNA with roles in the central metabolism - Bækkedal, Cecilie (RNA Biol, 2015)
The Spot 42 RNA is a 109 nucleotide long (in Escherichia coli) noncoding small regulatory RNA (sRNA) encoded by the spf (spot fourty-two) gene. spf is found in gamma-proteobacteria and the majority of experimental work on Spot 42 RNA has been performed using E. coli, and recently Aliivibrio salmonicida. In the cell Spot 42 RNA plays essential roles as a regulator in carbohydrate metabolism and uptake, and its expression is activated by glucose, and inhibited by the cAMP-CRP complex. Here we summarize the current knowledge on Spot 42, and present the natural distribution of spf, show family-specific secondary structural features of Spot 42, and link highly conserved structural regions to mRNA target binding.